Plan of action for carbapenem antibiotics sterility testing - S. I. Kuleshova; S. A. Protsak; S. A. Lisunova; G. Yu. Romanyuk; E. N. Semenova (Регуляторные исследования и экспертиза лекарственных средств)
The article proposes a plan of action for assessing effectiveness and reliability of sterility testing in terms of neutralization of antimicrobial activity of residual amounts of antibiotics remaining on the membrane filters during the analysis. It was demonstrated that the proposed plan of action helps to select appropriate test conditions that rule out the possibility of obtaining false negative results for antibiotics with high biological activity that are capable of sticking to membrane filters. The article demonstrates the need for a stepwise experimental selection of test conditions using different test microorganisms in order to determine a combination of several methods for neutralization of residual amounts of antibiotics which helps to reduce costs, given that satisfactory results may be obtained at any stage depending on the nature of an antibiotic drug. The article explicitly substantiates all stages involved in determination of the completeness of membrane filters cleaning from residual amounts of antibiotics using the example of meropenem. Based on results of experiments test conditions were selected for meropenem products that ensured reliable results of sterility testing.